PENGARUH UNIT-UNIT USAHA TERHADAP KINERJA KEUANGAN PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) GURU-GURU RAUNG SITUBONDO - Riski, Alfina; Wahyuni, Ika; Wiryaningtyas, Dwi Perwitasari (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
This study aims (1) to determine the partial effect of savings and loan business units, self-service business units and general fueling station business units on financial performance (2) to determine the simultaneous effect of savings and loan business units, self-service business units and station business units. general refueling on financial performance (3) to determine the effect of savings and loan business units, self-service business units and general refueling station business units which have a dominant influence on financial performance. The method used is multiple linear regression analysis, t test, f test, dominant test and coefficient of determination. The result of this research is multiple linear regression equation Y = 4.191 + 0.057 X1 + 0.052 X2 - 0.552 X3 + e. Partial testing is the savings and loan business unit (count )1,578 < t_table 2,042, the self-service business unit tcount 0.395 < ttable 2,036 and the general fuel filling station business unit -tcount -4.693 > -ttable -2,036. Thus, the savings and loan business unit, the self-service business unit and the general fueling station business unit have no effect on financial performance. Simultaneous testing of savings and loan business units, self-service business units and general fueling station business units has an effect on financial performance because the value of Fcount is 7.649 > Ftable 2.90. There is no dominant variable to influence the financial performance variable.